2015
DOI: 10.1111/add.13087
|View full text |Cite
|
Sign up to set email alerts
|

Risk of mortality on and off methadone substitution treatment in primary care: a national cohort study

Abstract: Among primary care patients undergoing methadone treatment, continuing in methadone treatment is associated with a reduced risk of death. Patients' risk of all-cause mortality increases following treatment cessation, and is highest in the initial 4-week period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 35 publications
2
51
0
4
Order By: Relevance
“…Multiple large-scale studies have found all-cause mortality to be significantly higher in patients after disengagement from buprenorphine or methadone maintenance therapy compared with all-cause mortality during treatment. (Bell, Trinh, Butler, Randall, & Rubin, 2009; Clausen, Anchersen, & Waal, 2008; Cousins et al, 2016) Although some very early disengagers may have sought buprenorphine or methadone treatment elsewhere, some patients may have died without treatment. This may partially explain this clinic’s low re-engagement rates of very early disengagers.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Multiple large-scale studies have found all-cause mortality to be significantly higher in patients after disengagement from buprenorphine or methadone maintenance therapy compared with all-cause mortality during treatment. (Bell, Trinh, Butler, Randall, & Rubin, 2009; Clausen, Anchersen, & Waal, 2008; Cousins et al, 2016) Although some very early disengagers may have sought buprenorphine or methadone treatment elsewhere, some patients may have died without treatment. This may partially explain this clinic’s low re-engagement rates of very early disengagers.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Overdoses frequently occur among persons who were recently discharged from detoxification programs, treatment, or criminal justice settings (Binswanger et al, 2007; Cousins, Boland, Courtney, et al, 2015; Ravndal & Amundsen, 2010; Sordo, Barrio, Bravo, et al, 2017; Strang, Mccambridge, Best, et al, 2003). Unintentional overdose death is often a consequence of untreated or improperly treated opioid use disorder (OUD), reflecting a long-standing addiction treatment gap in the United States and the difficulties patients face in accessing evidence-based care (Ghitza & Tai, 2014; Volkow, Friedan, Hyde, & Cha, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…26 During and after tapering, close contact with the patient should be maintained because discontinuation of maintenance carries high risks of relapse to the use of illicit drugs and overdoses that may lead to death. 11,52,53 The effectiveness of methadone maintenance is well established, and this drug is listed among "essential medications" by the World Health Organization. 11,45 Maintenance programs decrease mortality by approximately 50% among persons with opioid-use disorders, decrease acquisition of HIV infection and hepatitis, decrease crime and illicit-substance use, improve social functioning, and increase the rate of retention in rehabilitation programs.…”
Section: Methadone Maintenance Approachesmentioning
confidence: 99%